Cost-effectiveness analysis of app-delivered self-management support (selfBACK) in addition to usual care for people with low back pain in Denmark - Paul Jarle Mork; Jan Hartvigsen; Karen Søgaard; Louise Fleng Sandal; Mette Jensen Stochkendahl; Line Planck Kongstad; Cecilie Krage Øverås; Christian Volmar Skovsgaard (BMJ Open)
Objectives This study aims to investigate the cost-effectiveness of individually tailored self-management support, delivered via the artificial intelligence-based selfBACK app, as an add-on to usual care for people with low back pain (LBP).Design Secondary health-economic analysis of the selfBACK randomised controlled trial (RCT) with a 9-month follow-up conducted from a Danish national healthcare perspective (primary scenario) and a societal perspective limited to long-term productivity in the form of long-term absenteeism (secondary scenario).Setting Primary care and an outpatient spine clinic in Denmark.Participants A subset of Danish participants in the selfBACK RCT, including 297 adults with LBP randomised to the intervention (n=148) or the control group (n=149).Interventions App-delivered evidence-based, individually tailored self-management support as an add-on to usual care compared with usual care alone among people with LBP.Outcome measures Costs of healthcare usage and productivity loss, quality-adjusted life-years (QALYs) based on the EuroQol-5L Dimension Questionnaire, meaningful changes in LBP-related disability measured by the Roland-Morris Disability Questionnaire (RMDQ) and the Pain Self-Efficacy Questionnaire (PSEQ), costs (healthcare and productivity loss measured in Euro) and incremental cost-effectiveness ratios (ICERs).Results The incremental costs were higher for the selfBACK intervention (mean difference €230 (95% CI −136 to 595)), where ICERs showed an increase in costs of €7336 per QALY gained in the intervention group, and €1302 and €1634 for an additional person with minimal important change on the PSEQ and RMDQ score, respectively. At a cost-effectiveness threshold value of €23250, the selfBACK intervention has a 98% probability of being cost-effective. Analysis of productivity loss was very sensitive, which creates uncertainty about the results from a societal perspective limited to long-term productivity.Conclusions From a healthcare perspective, the selfBACK intervention is likely to represent a cost-effective treatment for people with LBP. However, including productivity loss introduces uncertainty to the results.Trial registration number NCT03798288.